Reflections on the Nicaragua v. Colombia case (2022): From the perspective of traditional fishing rights - Jingyao Wang; Qi Xu (Frontiers in Marine Science, 2023)
With respect to the Nicaragua v. Colombia case in 2022, whether Colombian fishermen in the San Andrés Archipelago, particularly the Raizales, have traditional fishing rights in the Nicaraguan Exclusive Economic Zone (EEZ) is one of controversial issues. Since Colombia is not a party to the United Nations Convention on the Law of the Sea (UNCLOS), the International Court of Justice (the Court or the ICJ) embodied customary international law as applicable law. It adopted a two-step method to examine Colombian claims and found that their fishermen did not enjoy traditional fishing rights. The Court found that affidavits of Colombian fishermen as major evidence were too sparse to prove the existence of a long-standing fishing practice. In light of a series of statements from the Nicaraguan President, there was a neither express nor implied recognition of traditional fishing rights of Colombian fishermen. This study reviews the ICJ’s judgment from three aspects. First, the paper will evaluate the Court’s (in)flexibility about the time requirement when examining the spanning period of a long-standing practice relating to traditional fishing activities. Second, concerning whether or in which circumstances the traditional fishing rights of a particular community can survive the establishment of the EEZ of another State, the Court found it unnecessary to examine this issue, the paper will also appraise potential legal impacts at this regard. Third, the Court did not identify Colombian claims of traditional fishing rights as indigenous rights, particularly for the Raizales. An increasing number of scholars of the law of the sea call for applying human rights norms to UNCLOS provisions, but the Court takes a cautious attitude in this regard. The paper will make more comments on the interaction between human rights law and the law of the sea.